Brevilin A Induces Cell Cycle Arrest and Apoptosis in Nasopharyngeal Carcinoma - Liu, Rui; Qu, Zhao; Lin, Yushan; Lee, Chi-Sing; Tai, William Chi-Shing; Chen, Sibao (Frontiers in Pharmacology, 2019)
Nasopharyngeal carcinoma (NPC) is one of the most common malignant cancers in Southeast Asia and Southern China. Centipeda minima extract (CME) had previously demonstrated anti-cancer effects in human NPC. Brevilin A, a sesquiterpene lactone isolated from Centipeda minima, has been reported to exhibit biological activities. In this study, we investigated its anti-NPC effect and further explored its molecular mechanisms. The effects of brevilin A were tested in the NPC cell lines CNE-1, CNE-2, SUNE-1, HONE1 and C666-1. Effects of brevilin A on cell viability were determined by MTT assay and cell cycle and apoptosis were detected by flow cytometry. The molecular mechanism of cell cycle regulation and apoptosis were investigated via Western blot. Results showed that brevilin A inhibited NPC cell viability in a concentration- and time-dependent manner. Brevilin A induced cell cycle arrest at G2/M, and induced apoptosis. Western blot results demonstrated that brevilin A could downregulate cyclin D3, cdc2, p-PI3K, p-AKT, p-mTOR and p-STAT3, while upregulating cleaved PARP, cleaved caspase 9 and Bax. Regulation of cyclin B1, cdk6, and Bcl-2 expression by brevilin A showed dynamic changes according to dose and time. In the tumor xenograft model, brevilin A could reduce tumor growth, at a similar magnitude to cisplatin. However, notably, whereas cisplatin treatment led to significant weight loss in treated mice, treatment with brevilin A did not, indicating its relative lack of toxicity. Taken together, brevilin A regulated cell cycle, activated the caspase signaling pathway, and inhibited PI3K/AKT/mTOR and STAT3 signaling pathways in vitro, and exhibited similar efficacy to the common chemotherapeutic cisplatin in vivo, without its associated toxicity. These findings provide a framework for the preclinical development of brevilin A as a chemotherapeutic for NPC.